On the ‘Discovery’ of Vitamin A - Semba, Richard D. (Annals of nutrition and metabolism, 2012)
Vitamin A is essential for normal growth, reproduction, immunity, and vision. The characterization of vitamin A spanned a period of about 130 years. During this long, incremental process, there is no single event that can be called the ‘discovery’ of vitamin A. The physiologist François Magendie conducted nutritional deprivation experiments with dogs in 1816 that resulted in corneal ulcers and high mortality – a finding similar to the common clinical situation in poorly fed, abandoned infants in Paris. In the 1880s, Nicolai Lunin showed that there was an unknown substance in milk that was essential for nutrition. Carl Socin suggested that an unknown substance for growth in egg yolk was fat soluble. Frederick Gowland Hopkins proposed in 1906 that there were ‘unsuspected dietetic factors’ that were necessary for life. In 1911, Wilhelm Stepp demonstrated that this essential substance in milk was fat soluble. The following year, Hopkins showed that there were ‘accessory factors’ present in ‘astonishingly small amounts’ in milk that supported life. Contrary to the dogma that all fats had similar nutritional value, in 1913, Elmer McCollum and Marguerite Davis at Wisconsin and Thomas Osborne and Lafayette Mendel at Yale showed butter and egg yolk were not equivalent to lard and olive oil in supporting the growth and survival of rats. The growth-supporting ‘accessory factor’ became known as ‘fat-soluble A’ in 1918 and then ‘vitamin A’ in 1920. Paul Karrer described the chemical structure of vitamin A in 1932. Harry Holmes and Ruth Corbet isolated and crystallized vitamin A in 1937. Methods for the synthesis of vitamin A came with the work of David Adriaan van Dorp and Jozef Ferdinand Arens in 1946 and Otto Isler and colleagues in 1947. Further work on the role of vitamin A in immunity and child survival continued until through the 1990s.